Performance Comparison of S-Band Antenna with Series Fed and Corporate Fed Microstrip Array - ., Srilakshmi.; Manikandan, R; Shaikh Thasleem Bhanu, T (International Journal of Engineering and Technology, 2018)
Present wireless communication system needs the development of cost-effective, less weight and low profile antennas to show a high performance over different frequency spectrum. In this paper, we have designed a simple, economical and optimal gain rectangular microstrip patch antenna array capable of operating in S-band (2 to 4 GHz) frequency. The analysis is made for 2x1 patch antenna array connected in both series fed and corporate fed type. We carried out our simulation using High Frequency Structure Simulator (HFSS) and based on the results obtained; it helps us to identify the effective type of an antenna array. The antennas were designed using Flame Retardant 4 (FR4) epoxy substrate material with Îµr=4.4 and the thickness of the substrate (h) were kept at 1.6mm with a loss tangent value of 0.02. We considered return loss, gain, radiation pattern and bandwidth as our performance parameters for both series fed and corporate fed type microstrip antenna array. We finally achieved a higher gain value of about 5.47dB for the microstrip patch antenna array connected using corporate fed type. Â Â